Análisis e implementación de una pico central híbrida solar eólica para generar 500w en la hacienda “la merced” ubicada en el barrio Santa Ana del Pedregal, Parque Nacional Cotopaxi en el periodo 2014 - Toapanta Aguilar, Rodrigo Sebastian (2016)
This work is aimed at the analysis and implementation of equipment for a hybrid system take in account resources wind and solar in the area, as it is the case of the Association of Livestock Producers Sincholagua, Hacienda "La Merced", for the generation of electricity, which will serve as a support for researching in the future. The implementation of clean renewable technologies are aimed to provide a solution to the search for cleaner and cost-effective alternatives in the long term, this will allow the Association of Livestock Producers Sincholagua, Hacienda "La Merced", don’t dependent completely from the plants power that provide energy to the country….